Spike-based time-domain analog weighted-sum calculation model for extremely low power VLSI implementation of multi-layer neural networks - Wang, Quan; Tamukoh, Hakaru; Morie, Takashi (Frontiers in Neuroscience, 2025)
In deep neural network (DNN) models, the weighted summation, or multiply-and-accumulate (MAC) operation, is an essential and heavy calculation task, which leads to high power consumption in current digital processors. The use of analog operation in complementary metal-oxide-semiconductor (CMOS) very-large-scale integration (VLSI) circuits is a promising method for achieving extremely low power-consumption operation for such calculation tasks. In this paper, a time-domain analog weighted-sum calculation model is proposed based on an integrate-and-fire-type spiking neuron model. The proposed calculation model is applied to multi-layer feedforward networks, in which weighted summations with positive and negative weights are separately performed, and two timings proportional to the positive and negative ones are produced, respectively, in each layer. The timings are then fed into the next layers without their subtraction operation. We also propose VLSI circuits to implement the proposed model. Unlike conventional analog voltage or current mode circuits, the time-domain analog circuits use transient operation in charging/discharging processes to capacitors. Since the circuits can be designed without operational amplifiers, they can operate with extremely low power consumption. We designed a proof-of-concept (PoC) CMOS circuit to verify weighted-sum operation with the same weights. Simulation results showed that the precision was above 4-bit, and the energy efficiency for the weighted-sum calculation was 237.7 Tera Operations Per Second Per Watt (TOPS/W), more than one order of magnitude higher than that in state-of-the-art digital AI processors. Our model promises to be a suitable approach for performing intensive in-memory computing (IMC) of DNNs with moderate precision very energy-efficiently while reducing the cost of analog-digital-converter (ADC) overhead.